Discovery of a selective dual-specificity tyrosine phosphorylation-regulated kinase 1B inhibitor with anti-adipogenic and anti-diabetic activities - Kang, Sein; Na, Yoon-Ju; Choi, Kyoung Jin; Jung, Won Hoon; Park, Areum; Im, Jeonghui; Park, Sung Bum; Koh, Byumseok; Lee, Joo-Youn; Hoe, Kwang-Lae; Kim, Heung Jae; Shin, Sang Joon; et al. (Frontiers in Pharmacology, 2025)
BackgroundDual-specificity tyrosine phosphorylation-regulated kinase 1B (DYRK1B) is implicated in metabolic diseases, with high expression linked to adipocyte differentiation and metabolic disorders. This study investigated the anti-adipogenic and anti-diabetic effects of a novel selective DYRK1B inhibitor, N-(4-(3-(4-methoxyphenyl)-1H-pyrazolo [3,4-b]pyridin-5-yl) phenyl)acetamide (KS-40070).MethodsThe efficacy of KS-40070 was evaluated using 3T3-L1 cells, adipose-derived mesenchymal stem cells (ADMSC), and diet-induced obesity (DIO) mice.ResultsTreatment with KS-40070 dose-dependently inhibited 3T3-L1 preadipocyte differentiation, reducing key adipogenic transcription factors like PPARγ and C/EBPα, along with related proteins. KS-40070 suppressed lipid accumulation by decreasing Akt-FOXO1A signaling and GSK3β expression. Importantly, these effects were abolished in DYRK1B knockdown cells, confirming DYRK1B's role. In DIO mice, KS-40070 suppressed body weight gain, food consumption, serum lipid levels, and adipose tissue mass. It also improved insulin resistance and glucose intolerance.ConclusionThese findings suggest that inhibiting DYRK1B with agents like KS-40070 presents a promising therapeutic strategy for obesity and type 2 diabetes.